2020
DOI: 10.7717/peerj.9527
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of human cervical adenocarcinoma mucus to identify potential protein biomarkers

Abstract: Background Cervical cancer is the most common gynecological cancer, encompassing cervical squamous cell carcinoma, adenocarcinoma, and other epithelial tumors. There are many diagnostic methods to detect cervical cancers but no precision screening tool for cervical adenocarcinoma at present. Material and methods The cervical mucus from three normal cervices (Ctrl), three endocervical adenocarcinoma (EA), and three cervical adenocarcinoma in situ (AIS) was collected for proteomic analysis. The proteins were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 45 publications
(45 reference statements)
0
15
0
Order By: Relevance
“…They include annexin, tropomyosin, 14-3-3 sigma, calreticulin, and anterior gradient protein. Utilizing iTRAQ based labelled proteomics, another study from human cervical mucus found possible protein biomarkers that are differently expressed between cervical cancer patients and healthy controls [ 51 ]. The study found significant differences in 237, 256, and 242 proteins, respectively, amongst the comparable groups (endocervical adenocarcinoma vs. control, cervical adenocarcinoma in situ vs. control, and cervical adenocarcinoma in situ vs. endocervical adenocarcinoma) [ 51 ].…”
Section: Proteomic Biomarkers Identified From a Variety Of Body Fluid...mentioning
confidence: 99%
See 2 more Smart Citations
“…They include annexin, tropomyosin, 14-3-3 sigma, calreticulin, and anterior gradient protein. Utilizing iTRAQ based labelled proteomics, another study from human cervical mucus found possible protein biomarkers that are differently expressed between cervical cancer patients and healthy controls [ 51 ]. The study found significant differences in 237, 256, and 242 proteins, respectively, amongst the comparable groups (endocervical adenocarcinoma vs. control, cervical adenocarcinoma in situ vs. control, and cervical adenocarcinoma in situ vs. endocervical adenocarcinoma) [ 51 ].…”
Section: Proteomic Biomarkers Identified From a Variety Of Body Fluid...mentioning
confidence: 99%
“…Utilizing iTRAQ based labelled proteomics, another study from human cervical mucus found possible protein biomarkers that are differently expressed between cervical cancer patients and healthy controls [ 51 ]. The study found significant differences in 237, 256, and 242 proteins, respectively, amongst the comparable groups (endocervical adenocarcinoma vs. control, cervical adenocarcinoma in situ vs. control, and cervical adenocarcinoma in situ vs. endocervical adenocarcinoma) [ 51 ]. However, more research is needed to establish the fact that those differentially expressed proteins from mucus can actually be represented as biomarkers for the diagnosis and treatment of cervical cancer [ 51 ].…”
Section: Proteomic Biomarkers Identified From a Variety Of Body Fluid...mentioning
confidence: 99%
See 1 more Smart Citation
“…In 2020, Ma et al [134] published a proteomic study of cervical adenocarcinoma in situ in which the proteome of normal cervical samples was compared with endocervical adenocarcinoma samples using iTRAQ marking followed by LC-MS-TOF. Cervical adenocarcinoma and endocervical adenocarcinoma are the two main types of CC, with the highest prevalence in young populations.…”
Section: Cervical-vaginal Fluidmentioning
confidence: 99%
“…Gene ontology (GO) analysis performed on 1056 differentially expressed proteins showed that the highest percentages corresponded to proteins related to metabolic processes, cellular processes, biological regulation, response to stimuli, and biological regulation processes. The authors concluded that APOA1 might be a candidate marker for cervical adenocarcinoma and a study target to determine the functional mechanisms of this disease [134].…”
Section: Cervical-vaginal Fluidmentioning
confidence: 99%